Mental models of organic weed management: Comparison of New England US farmer and expert models. Issue 4 (December 2014) - Jabbour, Randa; Zwickle, Sarah; Gallandt, Eric R.; McPhee, Katherine E.; Wilson, Robyn S.; Doohan, Doug
Abstract Weeds are a major challenge for organic farmers, yet we know little about the factors influencing organic farmers' weed management decisions. We hypothesized that farmers and scientist 'experts' differ in fundamental areas of knowledge and perceptions regarding weeds and weed management. Moreover, these differences prevent effective communication, outreach programming and research prioritization. An expert mental model, constructed primarily from interviews with research scientists and extension professionals, revealed expert emphasis on knowledge of ecological weed management as crucial for successfully implementing such strategies. We interviewed 23 organic farmers in northern New England, yielding an aggregate farmer mental model to compare with the expert model. Farmers demonstrated knowledge of the major concepts discussed by experts, but differed in emphasis. Farmers placed less emphasis on ecological complexity than experts. One-third of farmers interviewed discussed the potential role of weeds as indicators of soil nutrient status, a concept of which experts were skeptical. Farmer beliefs about the weed seedbank highlighted potential misconceptions regarding seed persistence, with one-fourth of farmers focusing on the concept that seeds can live for an exceptionally long time in the soil, while experts focused on the concept of the seed half-life. Farmers emphasized the role of experience, both their own and that of other farmers, rather than knowledge derived from scientific research. Farmers considered yield and the cost of time and labor as equally at risk because of weeds, whereas experts predominantly discussed yield loss. During discussions of management, both farmers and experts most emphasized risks associated with cultivation and benefits associated with cover cropping. These results have prompted us, first, to develop new educational materials focused on weed seed longevity and management of the weed seedbank, and, second, to conduct regional focus groups with farmers who prioritize fertility management in their efforts to control weeds, especially manipulations of soil calcium and magnesium.